2015
DOI: 10.1517/17425247.2016.1100166
|View full text |Cite
|
Sign up to set email alerts
|

Advances in intravesical therapy for urinary tract disorders

Abstract: Introduction Intravesical therapy is a valuable option in the clinical management of urinary tract disorders such as interstitial cystitis/ painful bladder syndrome (IC/PBS) and refractory overactive bladder. This review will cover the latest advances in this field using polymer and liposomes as delivery platform for drugs, protein and nucleic acids. Areas covered This review summarizes the significance of intravesical therapy for lower urinary tract disorders. The recent advancement of liposomes as a drug d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 113 publications
(129 reference statements)
0
30
0
Order By: Relevance
“…Animals were pretreated with ODN and siRNA before the exposure to insults (acetic acid and lipopolysaccharide), and the treatment efficacy was confirmed by functional and molecular end‐points. Liposomes can improve the bladder uptake of nucleic acids …”
Section: Liposomes + Nucleic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals were pretreated with ODN and siRNA before the exposure to insults (acetic acid and lipopolysaccharide), and the treatment efficacy was confirmed by functional and molecular end‐points. Liposomes can improve the bladder uptake of nucleic acids …”
Section: Liposomes + Nucleic Acidsmentioning
confidence: 99%
“…The change of T1 relaxation time of bladder wall tissue after instillation can be a measure of drug delivery . Another option is near‐infrared fluorescence imaging for low absorption and scattering of photons within the near‐infrared region in animals . The deeper penetration of near‐infrared light compared with visible wavelengths allows for the possibility of deeper‐tissue imaging, as well as the possibility of long‐term imaging without off‐target effects of excitation.…”
Section: Future Directionsmentioning
confidence: 99%
“…These studies were based on the intravenous administration of dexmedetomidine, which increases the risk of arrhythmia. [22] A large number of studies [23][24][25] showed that intravesical instillation is an effective way of drug administration, which exerts an obvious effect on the treatment of bladder-related diseases. Concurrently, the intravesical instillation of drugs can reduce the systemic response.…”
Section: Introductionmentioning
confidence: 99%
“…Local instillation therapy of the bladder is a generally accepted and widely used treatment modality of the bladder in different pathological conditions. Its advantages are the locally high concentration of the active drug and the reduced level of systemic side effects …”
Section: Introductionmentioning
confidence: 99%
“…Its advantages are the locally high concentration of the active drug and the reduced level of systemic side effects. 1 Intravesical instillation therapy is at present most frequently applied in cases of superficial bladder cancer to reduce the rate of local recurrence, 2 and in the treatment of IC/BPS. 3,4 Intravesical drug delivery has also been reported to be efficacious in chronic bacteriological bladder infections, 5 refractory overactive bladder, 6 and following pelvic radiotherapy.…”
Section: Introductionmentioning
confidence: 99%